Solid State Synthesis Of Barium Strontium Titanate At 850oC From Mechanically Activated BaCO3-SrCO3-TiO2 Mixture. - Teoh, Wah Tzu; Sato, Kazunori; Mohd Noor, Ahmad Fauzi (2007)

(untitled)
The influence of mechanical activation on the solid state reaction to synthesis Ba0.70Sr0.30TiO3 was studied. Thermal analysis of the raw materials and the activated BaCO3-SrCO3-TiO2 mixture was carried out.